(untitled) (Research, Society and Development, 2020)
Auxemma glazioviana Taub. (Boraginaceae), known as "white stick", is distributed in the states of Ceará and Rio Grande do Norte and is traditionally used in the treatment of cuts and wounds. The different biological activities are associated with the presence of quinones, a chemical compound widely occurring in the species. The objective of this study was to identify the main classes of secondary metabolites, quantify the total content of polyphenols, obtain the quinone fraction (FQ) and evaluate the antioxidant potential of the ethanolic extract of A. glazioviana and the fraction obtained. From the extract a phytochemical screening and quantification of total polyphenols was performed. The attainment and characterization of the quinone fraction was done through chromatographic techniques. The antioxidant potential of the extract and of the fraction was determined by the methods, DPPH●; capture of free radical ABTS●+, determination of the reduction power of Fe3+ ion (FRAP) and relative antioxidant capacity (CAR). The chemical prospection of the ethanolic extract revealed the presence of flavonoids. The quantification of total polyphenols was 4.4822 mg AG/g.extract. In the antioxidant analysis, extract and fraction presented significant results, in which EECCAG was more efficient when compared to FQ. The data show that EECCAG is potentially more efficient in antioxidant activity.